Transparansi Proses dalam Pelaksanaan Program Ketahanan Pangan Desa: Studi Kasus Desa Mekarrahayu, Kecamatan Margaasih, Kabupaten Bandung Tahun 2025 - Faqih Ragi; Iyep Saefulrahman (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Process transparency constitutes a critical dimension in village governance, particularly in managing food security programs that involve substantial public funds. This study examines the implementation of process transparency in the food security program of Mekarrahayu Village, Margaasih District, Bandung Regency in 2025, which allocated IDR 428,900,000 from the Village Fund for sheep farming development. Employing a qualitative method with semi-structured interviews and documentation involving 11 purposively selected informants, this research applies David Heald's (2006) process transparency framework, which focuses on the openness of planning procedures, program implementation mechanisms, and oversight and evaluation processes. The findings indicate that Mekarrahayu Village has established deliberative forums and oversight structures that conform to formal requirements. However, the results of deliberative processes have not been widely disseminated, the mechanism for determining program beneficiaries has not been conducted through an open and participatory process, and the involvement of supervisory institutions remains predominantly procedural. These conditions reveal a gap between the formal availability of procedures and the substantive openness of information accessible to the public. The study recommends that village governments prioritize active and inclusive communication strategies that extend beyond formal procedural compliance toward genuine information sharing that enables meaningful public participation in village program governance.